Time allocation of daughters-in-law and mothers-in-law in India: The role of education as bargaining power - Leena Bhattacharya (Global Labor Organization (GLO), 2023)
The paper addresses the less-researched topic of intrahousehold dynamics of female in-laws in developing countries by focusing on the bargaining between mother-in-law and daughter-inlaw and its influence on the latter's time allocation. Using the first nationally representative Time Use Survey of India, 2019, the paper answers two questions. First, how does the presence of the parents-in-law, particularly the mother-in-law, shape the daughter-in-law's distribution of time between paid and unpaid activities? Second, how does the relative bargaining power among the female in-laws affect the daughter-in-law's time allocation across different activities, where their education levels are used as indicators of bargaining power? The findings show that the daughter-in-law's participation in paid work increases in the presence of her mother-in-law and she allocates more time to paid work and less time to household production. The effect is evident for the daughters-in-law who co-reside with mothers-in-law who have completed at least secondary education. The mother-in-law's time allocated to household production and childcare increases when she co-resides with a daughter-in-law who has completed tertiary education. The father-in-law's presence consistently diminishes the daughter-in-law's engagement in paid work and increases both women's time spent on household production. Heterogeneity in results is observed by socio-religious groups and by the extent of patriarchy in the state of residence. Overall, the results suggest that policies that aim to increase women's education and promote gender-equal attitudes among men can enhance the daughter-in-law's bargaining power and time allocation.
Keywords: J22; J16; D13; 330; Intrahousehold bargaining; time allocation; education; gender; work; household production